Invasive shrubs amplify seasonal granivory, revealing optimal windows for seed survival following invasive shrub removal - Mark E. Fuka; John L. Orrock (Ecosphere)
Abstract Invasive shrubs dramatically reduce the biodiversity of native plants, making invaded areas important targets of conservation and restoration. Adding seeds of native plant species, in addition to the removal of invasive plants, is a potentially promising means for restoration of native plant communities. However, because seed survival may vary among seasons, it is essential to understand temporal patterns of seed survival. For example, dense habitats created by invasive shrubs exhibit seasonal changes in structure and food resources that could create seasonal variation in seed survival by altering the activity and abundance of native seed‐eating rodents. Despite the potential for invasive shrubs to generate seasonal changes in granivory, we lack experimental studies to evaluate changes in granivory caused by invasive plants over a full year. We mechanically removed the widespread invasive species common buckthorn (Rhamnus cathartica) from half of 14 sites (20 × 20 m) in a deciduous oak‐maple forest to track rodent and arthropod granivory of three native tree species, basswood (Tilia americana), black cherry (Prunus serotina), and sugar maple (Acer saccharum), and the invasive shrub R. cathartica over a year. Our results reveal that the effect of invasive shrubs on granivory changed across seasons. Seeds in invaded habitats experienced, on average, 25.9% higher seed removal than seeds in areas with R. cathartica removed, with the largest difference in removal occurring in winter. Seed removal was almost entirely due to rodent granivores that removed seeds at similar rates among species. These results indicate that, following removal of invasive shrubs, sowing seeds in winter may optimize seedling establishment by minimizing granivory. Our findings further reinforce the importance of removing invasive shrubs as an important restoration tool because invasions may amplify granivory throughout the year. Understanding the mechanisms that could be affecting seasonal granivory within invaded systems, the important role of rodent granivores, and the similarities in seed consumption between native and nonnative seeds is critical for continual conservation and restoration efforts aimed at promoting forest regeneration.